Implementasi Omnibus Law Dalam Sistem Ketenagakerjaan Indonesia Setelah Dikeluarkannya Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja - Muhamad Yosi Agustian; 1 Joni Anwar; Andri Meilansyah; Yunita Sari; Muhammad Ajadillah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
The Omnibus Law method was used in drafting Law Number 11 of 2020 concerning Job Creation. The Constitutional Court through Decision Number: 91/PUU-XVIII/2020 stipulated Law Number 11 of 2020 concerning conditional unconstitutional Job Creation, Then the Government issued Government Regulation in Lieu of Law (PERPU) Number 2 of 2022 concerning Job Creation. This study uses normative legal research methods. The problem in this writing is the implementation of the Omnibus Law in the Indonesian labor wage system and the position of the Omnibus Law in the Indonesian legal system and what factors lead to rejection of the Omibus Law. In conclusion, the implementation of the Omnibus Law has not been fully implemented and the position of the Omnibus Law is regulated in Article 64 paragraphs (1a) and (1b) of Law Number 13 of 2022 concerning Formation of Legislation and Factors for rejecting the Omnibus Law due to regulatory conflict. Suggestions, the Government and the People's Representative Council (DPR) should strictly issue regulations that are not contrary to the law in society and in the process of establishing the Omnibus Law, the public must be involved in a transparent manner and socialized in advance to the public.